Health-seeking experiences of women with obstetric fistula: a qualitative study at two fistula centres in Ghana - Ernest Maya; Richard Adanu; John Kuumuori Ganle; Adelaide Maria Ansah-Ofei; Ephraim Kumi Senkyire; Ernestina Asiedua; Sebastian Eliason (BMJ Open)
Objectives The study explored the health-seeking experiences of women with obstetric fistula from the onset of the condition until surgical treatment was obtained. It also describes their interactions with health staff and traditional healers.Design Exploratory, descriptive qualitative study.Setting Two secondary-level health facilities in the northern and central regions of Ghana; data collection took place in 2018–2019.Participants A purposive sample of 37 women who had experienced fistula resulting from childbirth and were awaiting fistula repair at the two fistula centres in Ghana was obtained.Data analysis Thematic analysis was used to analyse the data.Results Health-seeking experiences and behaviours of women with obstetric fistula were identified. Six major themes were generated: attribution and perceptions of fistula; competing alternatives/multiple sources of care; limited awareness and access to care; financial barriers; psychosocial challenges, and abuse by healers. The results indicate that the health-seeking experiences of women with obstetric fistula were characterised by long delays in care-seeking. The major themes and subthemes are presented with quotes from participants.Conclusion The women experienced winding pathways of treatment-seeking due to lack of awareness and incorrect attribution. The major barriers to health-seeking included poverty, challenges with transportation and inadequate repair centres. Increased awareness of obstetric fistula and access to repair centres could shorten the suffering women go through while awaiting fistula treatment. Improved awareness of obstetric fistula and establishment of more fistula centres would be beneficial.